Social and Individual Factors Influence Variation in Offspring Care in the Cooperatively Breeding Western Australian Magpie - Pike, Kyana N.; Ashton, Benjamin J.; Morgan, Kate V.; Ridley, Amanda R. (Frontiers in Ecology and Evolution, 2019)
In cooperatively breeding species, the level of investment in young can vary substantially. Despite receiving considerable research attention, how and why investment in young varies with cooperatively breeding group members remains unclear. To investigate the causes of variation in care of young, we assessed patterns of both helper and parental behaviour in the cooperatively breeding Western Australian magpie (Cracticus tibicen dorsalis). Observations of 19 helpers and 31 parents provisioning 33 broods raised in 11 different groups over two consecutive breeding seasons revealed substantial variation in offspring care behaviour. Our results suggest that the level of investment in young by helpers is strongly influenced by group size, chick age and morphological helper traits (including foraging efficiency, age and sex). Helping behaviour was facultative, and individuals from smaller groups were more likely to invest in helping behaviour. Overall, the number of broods receiving help was lowest during the nestling phase and highest during the fledgling phase. Female helpers provided more care than both male and juvenile helpers. We found that mothers invest more time in offspring care than do fathers, however fathers increase their effort in the presence of helpers while mothers do not. Overall, helper care was additive to parental care and therefore helping behaviour may be beneficial to the brood. Our research reveals that variation in offspring care in magpies is influenced by both social and morphological traits.